Assessment of HIV/AIDS educational intervention on stigma reduction among nurses: a quasi-experimental study - Gutierrez, John Mark (International Journal of Advanced Nursing Studies, 2014)
Background: In a setting where HIV/AIDS is highly endemic, nurses may respond to patients with increase fear of being at risk of acquiring HIV infection, decrease willingness to care, or both. The resulting stigmatization creates social barriers and discrimination between nurses and patients with HIV/AIDS. Objectives: This study aimed to increase nurses’ knowledge on HIV/AIDS and reduce HIV/AIDS-related stigma and discrimination in healthcare through HIV/AIDS educational intervention. Methods: This quasi-experimental study was carried out in all nursing departments of Shaqra General Hospital from February to April 2014. Nurses (n = 58), meeting the eligibility criteria, were included in the sample and were non-randomly assigned in one-group pre-test and post-test using purposive sampling technique. Results: The results of the pre- and post-intervention phases were compared using paired-sample t-test. Significant increase in nurses’ knowledge was demonstrated following HIV/AIDS educational intervention (p = 0.000). HIV/AIDS educational intervention was significantly associated with less stigmatization for ‘attitudes towards imposed measures’ (p = 0.002). In pre-intervention phase, the greatest stigmatizing attitude was observed in statement concerning the need for screening all inpatients for HIV/AIDS. The assessment at pre- and post-intervention for ‘comfortableness dealing with HIV/AIDS patients’ did not differ significantly, indicating least stigmatizing attitude. However, a statistical significant difference (p = 0.044) on nurses’ overall attitude towards patients with HIV/AIDS was detected between pre- and post-intervention assessment. Pooled mean revealed no observed discriminatory act among nurses at pre- and post-intervention assessment. Conclusion: The utilization of HIV/AIDS educational intervention improved nurses’ theoretical knowledge about HIV/AIDS. Although nurses’ knowledge on HIV/AIDS was improved significantly, their attitudes of blame or judgment as well as their comfortableness dealing with HIV/AIDS patients have not changed. The effectiveness of HIV/AIDS educational intervention in reducing HIV/AIDS-related discrimination as well as its impact on nurses’ attitudes towards patients with HIV/AIDS warrants further investigation. Keywords: Attitudes, Discrimination, Educational Intervention, HIV/AIDS, and Stigma.